Key topics in coaching psychology - Jones, Rebecca J.; Andrews, Holly (BPS key topics in psychology, 2026)
Offering a concise and easy-to-read introduction to the subject, this book deals with key topics in the study of coaching psychology. It explains what coaching psychology is, when and why it is used, and what research can tell us about how and why it works.The book opens with an exploration of the key foundations of coaching psychology, including how it is defined, where it began, and how has it developed. This is followed by an overview of the key theories informing coaching psychology: person-centred theories, goal-setting theory, adult learning theory, and the main theoretical approaches to coaching (behavioural coaching, cognitive behavioural coaching, psychodynamic coaching, and systemic coaching). The authors discuss the key methodologies used in coaching psychology research, covering both quantitative and qualitative approaches, before exploring the impact of coaching psychology on five areas of practice: coaching in the workplace, career coaching, coaching in education, life coaching, and health coaching. Finally, they suggest future directions for the field by examining emerging areas in research and practice.Academically informed, and fully integrating key theories with application in coaching practice, this book gives readers a comprehensive yet accessible understanding of coaching psychology. Key Topics in Coaching Psychology is the ideal resource for undergraduate and postgraduate students of coaching psychology and occupational psychology, business, and leadership, as well as anyone with an interest in learning more about coaching psychology.